From Symbionts to Societies: How Wood Resources Have Shaped Insect Sociality - Dillard, Jacqueline; Benbow, Mark Eric (Frontiers in Ecology and Evolution, 2020)
Sociality has independently arisen in several wood-dwelling insect lineages. Despite this seemingly important ecological trait, little attention has been devoted to understanding how the properties of decaying logs as nest or food resources favor the evolution of cooperative social groups. In this review, we evaluate the current literature on wood-dwelling social insects to identify the key features of wood habitats that has led to the repeated evolution of social behavior. We emphasize important roles of both the structural properties of wood as well as the microbial symbionts and pathogens with which wood-dwelling social insects co-evolved. Wood-tissue is structural resilient, and thus provided an enclosed, defensible nest site for early wood-feeding insect groups. This resilience enabled the long-term persistence of family groups, and was likely a key feature in the transition towards more complex eusocial societies. The dense structure of wood, however, also makes it a nutritionally poor food source. Insects that both live and feed on this resource developed complex mutualisms with prokaryote and fungal symbionts to digest this resource. Parental care likely evolved to ensure adequate nutrition for offspring in this environment by allowing parents to both provision and transfer microbial symbionts to offspring. Pathogenic microbes are also abundant in nests constructed in wood-tissue, and social adaptations such as allogrooming and nest maintenance may have evolved in response to microbial invaders. In general, the dynamic relationship between insects, microbes, and the wood-tissue that they inhabit was a critical component in the evolution of sociality in this habitat.